1984
DOI: 10.1180/minmag.1984.048.348.05
|View full text |Cite
|
Sign up to set email alerts
|

Some aspects of Tertiary acid magmatism in NE Ireland

Abstract: ABSTRACT. Geochemical data (including REE determinations) are presented for all five Mourne Mountains granites and three Northern Ireland rhyolites. These confirm (1) the extremely fractionated nature of some of the rocks (Sr and Ba < 10 ppm, Rb > 400 ppm, Eu/Eu* < 0

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 21 publications
2
28
0
Order By: Relevance
“…Stevenson et al (2007b) outlined the key criteria that Richey (1928) used to invoke cauldron subsidence in this plutonic complex sensu Clough et al (1909). Revisions of Richey's (1928) original mapping in both centres (Emeleus 1955;Hood et al 1981;Meighan et al 1984) involved only minor modifications of Richey's original framework and the ring-dyke cauldron subsidence model persisted (for a summary see Cooper & Johnston 2004, pp. 182-187) until Stevenson et al (2007b) revealed magmatic fabrics in the Eastern Mourne granite using anisotropy of magnetic susceptibility (AMS) measurements.…”
Section: Laccoliths As Opposed To Cauldron Subsidencementioning
confidence: 98%
See 1 more Smart Citation
“…Stevenson et al (2007b) outlined the key criteria that Richey (1928) used to invoke cauldron subsidence in this plutonic complex sensu Clough et al (1909). Revisions of Richey's (1928) original mapping in both centres (Emeleus 1955;Hood et al 1981;Meighan et al 1984) involved only minor modifications of Richey's original framework and the ring-dyke cauldron subsidence model persisted (for a summary see Cooper & Johnston 2004, pp. 182-187) until Stevenson et al (2007b) revealed magmatic fabrics in the Eastern Mourne granite using anisotropy of magnetic susceptibility (AMS) measurements.…”
Section: Laccoliths As Opposed To Cauldron Subsidencementioning
confidence: 98%
“…1) and heralded the breakup of North America and Eurasia c. 55 Ma (Jolley & Bell 2002). The Mourne Granites are anorogenic and the granitic melt formed by fractionation of basalts derived from plume-driven mantle melting under intact continental lithosphere (Meighan et al 1984;Kent & Fitton 2000) but, as has been shown for other British and Irish Palaeogene Igneous Province centres, may have had melt contributions from crustal contamination sources (e.g. Geldmacher et al 2002;Troll et al 2005).…”
Section: Mourne Granitesmentioning
confidence: 98%
“…Meighan 1979, Meighan et al 1984, Thorpe et al 1990), although it must be noted that Stone (1988Stone ( , 1990) assigns general S-type status to the Lundy intrusions. The paucity of published isotopic data factor (Table 3) is particularly serious for parts of this sector, especially for O. Recognising this and the importance of information for several isotopic systems, new data for Arran (O) and northeastern Ireland (O, Nd, Sr) are summarised and discussed in relation to the northern sector.…”
Section: New Isotopic Data For the S Sector Of The Btipmentioning
confidence: 99%
“…Notes'. Major elements and Sr were determined by X-ray fluorescence analysis, Ce, Yb and Eu by neutron activation analysis (as in Meighan et al 1984 on July 5, 2015 specialpapers.gsapubs.org Downloaded from 3.1. O isotopic data: N Arran, Ailsa Craig and northeastern Ireland Table 6 summarises new O isotopic data for the granitic rocks of N Arran (the coarse biotite granite and later, more fractionated, 'fine' biotite granite) and the Mourne Mountains (amphibole-biotite granites G1 and G5 together with the very fractionated biotite granites G2, G3 and G4: McCormick et al under review).…”
Section: New Isotopic Data For the S Sector Of The Btipmentioning
confidence: 99%
See 1 more Smart Citation